Intrinsic sodium occurrence in Zhundong coal: Experimental observations and molecular modeling. (1st December 2021) - Sun, Cen; Wei, Xiaolin; Kang, Running; Bin, Feng; Li, Sen
Highlights: Semi-quantitative analysis of 23 Na CP/MAS NMR were conducted. Molecular occurrence model of sodium was constructed via computational chemistry. Adsorption position of sodium was investigated by computational chemistry. The real way of organic sodium bonding to the coal was discussed and observed. Abstract: Detailed intrinsic sodium occurrence for future research on migration, release, and catalyst effect behavior of sodium is necessary. Complementary characterizations, such as 13 C CP/MAS NMR, FT-IR, 23 Na CP/MAS NMR, XPS, elemental composition analysis, and sequential extraction experiments, were employed to elucidate the actual compound form of sodium as well as Zhundong coal's structural features. Thus, a molecular occurrence model of sodium in Zhundong coal was constructed based on its structural characteristics via computational chemistry. The occurrence model of alkali metals in Zhundong coal, including their compound form, relative content, and distribution properties, was investigated at the microstructural level. Preliminary results show that the amorphous cell formula of Zhundong coal is (C2080 H980 O380 N30 S10 Na) n . Organic oxygen in Zhundong coal was 67.7% hydroxyl (ethoxy), 15.5% carbonyl, and the remaining 16.8% was attributed to carboxyl. Combined with the 23 Na CP/MAS NMR and sequential extraction experiment, organic sodium accounts for 18.01% of the total. Most inorganic sodium (81.99%) is present as hydrated sodium ion (75.08%), while a small part is present as NaCl crystal phase (3.34%) insoluble-sodium account for 3.57%. Calculated 13 C NMR, FT-IR, and 23 Na NMR spectra of the proposed model agree well with the experimental spectra suggesting that the molecular occurrence model of sodium in Zhundong coal is a particularly convincing model at the approximate condition of statistical average. The highest negative electrostatic potential area is near the carboxyl group and may be attributed to organic sodium absorption sites; the hydroxy or phenoxy group nearby may form additional coordination bonds to sodium, indicating the reflection of the complexity of the Na chemical environment as concluded from 23 Na CP/MAS NMR.